Pembuatan paving blok geopolimer dari limbah abu terbang batu bara (Fly Ash) di Kelurahan Pematang Kapau Tenayan Raya Pekanbaru - Aman Aman; Amun Amri (Unri Conference Series: Community Engagement, 2019)
The use of coal as fuel for PLTU Tenayan Raya Pekanbaru produces waste in the form of fly ash and bottom ash. Fly ash has high silica and alumina content which has the potential to replace cement. The resulting fly ash is partly not utilized and is piled up in the ash disposal area and has the potential to cause water and soil pollution. The increasing use of coal, the environmental burden will be heavier and needs to be anticipated by finding optimal utilization of coal fly ash waste. Based on the description above, community service activities have been carried out in Pematang Kapau Village, Tenayan Raya Pekanbaru District in the form of socialization and training on the use of fly ash waste as a material for making geopolymer paving blocks without using portland cement which has been used in the process of making paving blocks and other building materials. From the results of the above training activities obtained geopolymer paving blocks with specifications rectangular shape with a length of 21 cm, width 10 cm and height 8 cm, gray color and the test results obtained compressive strength of 40.87 MPa into SNI quality standard A.